2018
DOI: 10.1111/1460-6984.12381
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ views of the training, use and maintenance of phonetic transcription in speech and language therapy

Abstract: As many clinicians found it difficult to learn transcription, there is an opportunity to provide more transcription practice both in and beyond the classroom. Despite most clinicians feeling equipped to undertake transcription upon completion of their training, and a large majority requiring transcription for their role, a theory/practice gap is apparent in the relatively small number of clinicians using narrow transcription exclusively, and those not using it expressing lack of confidence in their skills. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Such a possibility would be increased if there were opportunities for continuing education in phonetic transcription. Knight et al .’s (2018) survey of phonetic transcription practices among SLPs/SLTs revealed that many practitioners perceived the lack of availability of continuing education in phonetic transcription to be a reason why they used it only inconsistently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a possibility would be increased if there were opportunities for continuing education in phonetic transcription. Knight et al .’s (2018) survey of phonetic transcription practices among SLPs/SLTs revealed that many practitioners perceived the lack of availability of continuing education in phonetic transcription to be a reason why they used it only inconsistently.…”
Section: Resultsmentioning
confidence: 99%
“…Knight et al . (2018) reported great variability among SLPs/SLTs in the UK in their regular use of phonetic transcription, as well as in the amount of phonetic detail that they typically use in their practice. In short, group differences may be due to many factors: differences in perceptual acuity, differences in practice patterns or to some combination of these factors.…”
Section: Continuous Rating Scales and Speech Assessmentmentioning
confidence: 99%
“…Phonetic transcription is a core skill for practicing speech and language therapists (SLTs) worldwide which allows them to assess disordered speech patterns and identify the nature of any delay/disorder that may be present (Enderby, et al, 2009;Howard & Heselwood, 2002;Knight, Bandali, Woodhead, & Vansadia, 2018). Accurate phonetic transcription based on a careful auditory analysis of speech and following the conventions of the IPA is the starting point for diagnosis and treatment of many clients.…”
Section: Transcriptionmentioning
confidence: 99%
“…This study investigates the views and experiences of final year SLT students regarding the training in phonetic transcription they received in university, with the aim to identify what poses difficulties for them and what could be done to enhance their learning. Responses from 40 participants representing one cohort of SLT students, graduates of a particular year, were collected using an online questionnaire based, with some changes, on Knight et al (2018).The majority of the respondents consider phonetic transcription an important professional skill and plan on maintaining it after graduating. Learning phonetic transcription was easy/quite easy for 57% of the respondents, however, the confidence in transcription skills was rather low: 70% of them reported not being confident and fully equipped to enter the 2 workforce with their transcription skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation